Analysis Of Family Conflict of Child Victims Sexual Violence in Palembang City - Arianti, Yosi; Soraida, Safira; Isyanawulan, Gita; Wulindari, Adetia (POPULIKA, 2025)
Sexual violence against children is a violation of human rights, which has a significant impact on the psychological and social conditions of the victims. This research explores the conflict between victims' families in Palembang City through a qualitative approach using observation and interview methods. The informants comprised 4 victims' families, 4 community members, and 1 representative of the Woman Crisis Center. Data analysis using Nvivo software reveals that family conflicts are often triggered by differences in views in dealing with the impact of victims, which are influenced by socio-cultural factors. Family support, including emotional, instrumental, information, and appreciation, has proven crucial in the recovery process. The results of this research provide insight into the impact of sexual violence on families and provide more effective recommendations for handling similar cases. Keywords: Conflict; Sexual Violence; Children; Family; Palembang City.